2016
DOI: 10.1158/1078-0432.ccr-14-3017
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Selection Shapes the T-cell Repertoire in Chronic Lymphocytic Leukemia

Abstract: Purpose: The role of antigen(s) in shaping the T-cell repertoire in chronic lymphocytic leukemia, although relevant for understanding malignant cell interactions with cognate T cells, is largely unexplored.Experimental Design: Here we profiled the T-cell receptor b chain gene repertoire in 58 chronic lymphocytic leukemia patients, focusing on cases assigned to well-characterized subsets with stereotyped clonotypic B-cell receptor immunoglobulins, therefore those cases most evidently selected by antigen (subset… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 47 publications
7
37
0
Order By: Relevance
“…In these areas, CLL cells are interspersed with T cells, which co-localize with Ki67 + proliferating CLL cells, suggesting that T cells provide help to the CLL cells for promoting their expansion (46). PB T cell numbers in untreated CLL patients are elevated and oligoclonal (4, 7), and emerging data indicate that these CLL T cells expand in an antigen-dependent fashion, in a process that resembles normal adaptive immune responses to antigen (810). Prior studies reported about T cell repertoire skewing and oligoclonality in CLL patients based on flow cytometric analysis, spectratyping (9, 11–13), and T cell receptor beta sequencing (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these areas, CLL cells are interspersed with T cells, which co-localize with Ki67 + proliferating CLL cells, suggesting that T cells provide help to the CLL cells for promoting their expansion (46). PB T cell numbers in untreated CLL patients are elevated and oligoclonal (4, 7), and emerging data indicate that these CLL T cells expand in an antigen-dependent fashion, in a process that resembles normal adaptive immune responses to antigen (810). Prior studies reported about T cell repertoire skewing and oligoclonality in CLL patients based on flow cytometric analysis, spectratyping (9, 11–13), and T cell receptor beta sequencing (10).…”
Section: Introductionmentioning
confidence: 99%
“…PB T cell numbers in untreated CLL patients are elevated and oligoclonal (4, 7), and emerging data indicate that these CLL T cells expand in an antigen-dependent fashion, in a process that resembles normal adaptive immune responses to antigen (810). Prior studies reported about T cell repertoire skewing and oligoclonality in CLL patients based on flow cytometric analysis, spectratyping (9, 11–13), and T cell receptor beta sequencing (10). TCRαβ diversity is generated by random rearrangements of V and J segments in the TCRα gene and V, D, and J segments in the TCRβ gene, concurrent with non-templated nucleotide insertions and deletions at the junctions (N-region); the resulting NDN region along with short segments of the flanking V and J genes comprise the complementarity-determining regions 3 (CDR3) of the TCR, which is primarily responsible for recognition of antigenic peptides (14).…”
Section: Introductionmentioning
confidence: 99%
“…In combination with the tumor‐shared and organ‐specific clonotypes with their frequencies, the TCR beta overlap rates and genetic distance between the initial primary NPCs and the subsequently developed distant metastatic tumors in the same patient after chemoradiotherapy were still up to 17.5–45.5% and close to 1.2–4.7, respectively, in contrast to the relatively long genetic distance from 27.4 to 32,518.6 between different NPCs. Our results demonstrated that a few common subsets of T‐cell clones of TILs found in primary NPCs were persistently juxtaposed to distant metastatic NPC cells regardless of anatomic location, physiological microenvironment and developmental time of metastasis (Table ) and were not matched to any known T‐cell clones specific to EBV, other viruses or neoantigens in the public databases despite the persistent presence of EBV in metastatic epithelial cancer cells …”
Section: Resultsmentioning
confidence: 89%
“…We next compared the 302,452 in‐frame TCR beta CDR3 amino acid sequences from the EBV‐associated NPC‐infiltrating lymphocytes against the public database sequences . Only 18 of the sequences were found to have identical matches to the known CD8 + T‐cell clones corresponding to EBV infection and were specific for the epitopes of BZLF1 or BMLF1 of the EBV lytic proteins in 32 patients (38%) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Their very early stages remain unknown but considering behaviour of cells in one of leukaemias (chronic B-cell laukaemia) [90,146], certain hypotheses can be suggested. Normal B lymphocytes of CD19 + CD5 + subpopulation continuously produce antibodies and in that function require no activation by T lymphocytes.…”
Section: Development Of Systemic Tumours On the Example Of B-lymphocymentioning
confidence: 99%